A new joint process optimisation methodology for pharmaceutical destructive characteristics: a statistical approach. (1st January 2012) - Truong, Nguyen Khoa Viet; Nha, Vo Thanh; Kim, Chul-Soo; Dizon, Rod Lester L.; Hong, Sung Hoon; Shin, Sangmun
In current pharmaceutical research and development, not many robust design (RD) and tolerance design (TD) approaches have been applied, although many researchers and practitioners have realised the importance of process design concepts. Pharmaceutical characteristics often involve different types of destructive measurements, such as hardness, friability, and disintegration in drug development and manufacturing processes. The primary objective of this paper is to develop an integrated robust-tolerance design methodology for handling destructive quality characteristics on pharmaceutical study. A statistical TD optimisation method, which incorporates consumer and producer risk, is proposed that uses a surrogate variable that is strongly correlated with the destructive quality characteristic. Finally, a pharmaceutical case study is performed for verification purposes. In the case study, a comparison between two RD optimisation models (i.e., dual-response and mean squares error models) is also conducted.